2016
DOI: 10.1002/gps.4453
|View full text |Cite
|
Sign up to set email alerts
|

An association between belief in life after death and serum oxytocin in older people in rural Japan

Abstract: Our findings could be interpreted differently depending on whether the anxiogenic or anxiolytic function of the oxytocin system is considered. Greater endorsement of afterlife beliefs may reduce secure attachment. Alternatively, based on the literature suggesting that basal levels of oxytocin are lower in those with reduced relational distress or anxiety, afterlife beliefs may play a role in these reductions. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 43 publications
3
35
1
Order By: Relevance
“…Baseline serum oxytocin levels were higher in women (0.123 ± 0.130 ng/ml) than in men (0.042 ± 0.052 ng/ml) as reported previously ( Imamura et al , 2017 ; Marazziti et al , 2019 ). The educational background was slightly higher in men (11.43 ± 2.53 years) than in women (9.41 ± 1.63 years).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Baseline serum oxytocin levels were higher in women (0.123 ± 0.130 ng/ml) than in men (0.042 ± 0.052 ng/ml) as reported previously ( Imamura et al , 2017 ; Marazziti et al , 2019 ). The educational background was slightly higher in men (11.43 ± 2.53 years) than in women (9.41 ± 1.63 years).…”
Section: Resultssupporting
confidence: 84%
“…This study was a longitudinal study. The survey was conducted in Kurokawa-cho, Imari, Saga Prefecture, Japan, among people aged 65 years and older as reported previously ( Nabeta et al , 2014 ; Matsushima et al , 2015 ; Imamura et al , 2017 ). Kurokawa-cho is in northwestern Saga Prefecture and is a rural town somewhat removed from urban areas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, in most cases, no sex differences were found [36-39], but there is also evidence of elevated levels in men [40]. Only one study [41] reported higher OT levels in older women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…All samples were analyzed in duplicate. Measurements were performed according to the manufacturer's instructions and based on our experiences as previously reported [50][51][52][53] .…”
Section: Assessment Of Cognitive Functionmentioning
confidence: 99%